Clinicopathological and predictive value of MAIT cells in non-small cell lung cancer for immunotherapy - Dongyan Shi; Lin Lin; Yun Chen; Jian Liu; Lin Shi; Jinying Lu; Da Zhong; Meijuan Song; Wenhua You; Wen-Hui Li (Journal for ImmunoTherapy of Cancer)
Background Immune-checkpoint inhibitors (ICIs) remain ineffective in a large group of non-small cell lung cancer (NSCLC) patients. Mucosal-associated invariant T (MAIT) cells, a population of unconventional innate-like T lymphocytes abundant in the human body, play important roles in human malignancies. Little is known about the immune characteristics of MAIT cells in NSCLC and correlation with prognosis and response rate of ICIs treatment.Methods To investigate the distribution, activation status, and function of MAIT cells in NSCLC patients and their correlations with anti-PD-1 immunotherapy, MAIT cells in peripheral blood, tumor and paratumor samples from NSCLC patients with or without anti-PD-1 immunotherapy were analyzed using flow cytometry and single-cell RNA-sequencing.Results MAIT cells were enriched in the tumor lesions of NSCLC patients migrating from peripheral blood via the CCR6-CCL20 axis. Both peripheral and tumor-infiltrating MAIT cells displayed an exhausted phenotype with upregulated PD-1, TIM-3, and IL-17A while less IFN-γ. Anti-PD-1 therapy reversed the function of circulating MAIT cells with higher expression of IFN-γ and granzyme B. Subcluster MAIT-17s (defined as cells highly expressing exhausted and Th17-related genes) mainly infiltrated in the non-responsive tissues, while the subcluster MAIT-IFNGRs (cells expressing genes related to cytotoxic function) were mainly enriched in responsive tissues. Moreover, we found predictive value of circulating MAIT cells for anti-PD-1 immunotherapy in NSCLC patients.Conclusions MAIT cells shifted to an exhausted tumor-promoting phenotype in NSCLC patients and the circulating MAIT subset could be a predictor for patients who respond to anti-PD-1 immunotherapy.